INVESTIGATION ON ACTIVITIES OF METAL OXIDES CATALYZED AMMONIA BORANE HYDROLYSIS - Filiz, Bilge Coskuner; Piskin, Sabriye (YILDIZ TECHNICAL UNIV, 2016)
In the present study, the activities of metal oxide - catalyzed ammonia borane (NH3BH3, AB) hydrolysis were investigated. Two non-noble metal oxide catalysts, cobalt oxide (Co3O4) and copper oxide (CuO), were synthesized by sol-gel method and catalytic activity tests were performed. The comparative kinetic analyses were investigated via Power Law and Bimolecular kinetic models. Hydrogen generation rates were achieved 4381.20 ml H-2.g(-1)cat.min(-1) and 835.04 ml H-2.g(-1)cat.min(-1) for Co3O4 and CuO metal oxides catalysts, respectively. Despite the different hydrogen generation rates of metal oxides catalysts, both metal oxides had similar apparent activation energy as 46.28 kJ.mol(-1) for Co3O4 and 45.64 kJ.mol(-1) for CuO with free of reactant concentration behaviors. According to the bimolecular kinetic model investigations, Co3O4 had stronger relationship with NH3BH3. Co3O4 metal oxide catalyst was found to be more active for NH3BH3 hydrolysis in order to generate hydrogen gas for practical energy applications.
Keywords: Metal oxides; ammonia borane; reaction kinetic; hydrogen; hydrolysis; ONE-STEP SYNTHESIS; HYDROGEN GENERATION; SODIUM-BOROHYDRIDE; NANOPARTICLES; DEHYDROGENATION; MECHANISM; NICKEL; CU; Engineering